Empowering Waqf Land with SMART-K and Vertiqua in Muhammadiyah Sukabumi City - Milla, Amalia Nur; Dindin, Ujang; Basori, Yana Fajar FY. (Pascasarjana Universitas Mataram, 2024)
This community empowerment is carried out through the utilization of waqf land in the form of two large ponds with an area of about 500 m2, then 5 classrooms that have not been used for a long time so that their condition is neglected. The purpose of this activity is to overcome the existing problems, namely the water channel to the pond that has not been repaired, the quality of the pond that is not adequate to be used as a cultivation pond, the manager, namely the group formed by the PDM, does not have experience and knowledge in fish farming. The method carried out as a solution to the existing problems is in the form of fish farming management training by improving the quality of ponds for cultivation through SMART-K (Aquaculture Management System and Technology Engineering). Training on vertiqua, land-saving fish farming and utilizing empty space as a place for fish farming. The results achieved were the quality of the pond was improved and koi fish cultivation was carried out through SMART-K, the empty room was used for catfish cultivation using tarpaulin ponds, vertiqua gen 2 was made as a technology for land-saving fish farming. The sustainability of this activity has the potential to be used as a place for fish farming training for the general public and education for the younger generation such as school children